THE CONCEPT OF CREATING A NEW MODEL OF THE SYSTEM OF INFORMATION AND LEGAL SUPPORT AND EDUCATION OF THE POPULATION IN THE FIELD OF ECOLOGY - Фирюза Мухитдинова (Journals Park Publishing, 2024)
The article deals with the problems of the environment, ecology of the modern world. Since today in the world there is an extremely unfavorable ecological situation: forests are dying, rivers are becoming shallow, seas are becoming poorer, surface, underground and sea waters, atmospheric air are being polluted, soils are being polluted and depleted, various species of animals and plants are disappearing, the number of man-made and technological accidents and disasters is increasing. This is manifested in the current qualitative growth of cooperation between subjects of international law. It is the international legal mechanisms for regulating the activities of states and international organizations aimed at preserving the human environment through the prevention, reduction and maximum possible limitation of adverse impacts on nature in unity with national legal measures that open the way to achieving harmony between society and nature. In solving this problem, on the way to reducing the global environmental problem, a comparative analysis of the environmental legislation of the countries of the world is of practical importance. This work concerns the identification of similarities and differences in the environmental legislation of Uzbekistan, the CIS countries, Central Asia, as well as the United Kingdom, Canada and the Netherlands and is aimed at applying positive foreign experience in the field of environmental protection in Uzbek legislative practice, taking into account the existing trends in the world and the outlined guidelines.
Keywords: Legal regulation, protection, environment, environmental, legislation, atmosphere, air, water, comparison, analysis, comprehensive environmental protection laws